1996
DOI: 10.1093/ajcn/63.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of orally and intravenously administered riboflavin in healthy humans

Abstract: The pharmacokinetics and utilization (flavocoenzyme synthesis) of orally and intravenously administered riboflavin in healthy humans were assessed. After the determination of circadian rhythms of riboflavin concentrations in blood plasma and urine of four males and five females (control period), each of these subjects received three different oral riboflavin doses (20, 40, and 60 mg) and one intravenous bolus injection of riboflavin (11.6 mg). Vitamins were administered in a randomized, cross-over design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 28 publications
6
139
1
1
Order By: Relevance
“…the coenzyme forms of vitamin B 2 were analyzed in total as FMN. The apparent discrepancies between our sample processing and that published by Zempleni et al 4) can be attributed in part to different temperature conditions and anticoagulants. Notably, we used a large excess of EDTA, which showed to inhibit the enzymatic activity that hydrolyzes FAD and FMN.…”
Section: Hydrolysis Of Fad In Rat and Human Plasmacontrasting
confidence: 82%
See 1 more Smart Citation
“…the coenzyme forms of vitamin B 2 were analyzed in total as FMN. The apparent discrepancies between our sample processing and that published by Zempleni et al 4) can be attributed in part to different temperature conditions and anticoagulants. Notably, we used a large excess of EDTA, which showed to inhibit the enzymatic activity that hydrolyzes FAD and FMN.…”
Section: Hydrolysis Of Fad In Rat and Human Plasmacontrasting
confidence: 82%
“…Because of a rapid hydrolysis of FAD in plasma after sample collection, the coenzyme forms of VB 2 were determined in total as FMN by acid hydrolysis. [4][5][6] Therefore, simultaneous determinations of RF, FMN and FAD in plasma have not widely used for pharmacokinetic studies of orally and intravenously administered VB 2 in animals and humans.…”
mentioning
confidence: 99%
“…In addition, the subject of riboflavin excretion has gained increasing attention. Jusko et al (18,19) and others (7,25,40,45) demonstrated saturable renal reabsorption and accumulation of riboflavin. Therefore, riboflavin transporters are thought to be essential for the maintenance of riboflavin homeostasis in the intestine and kidney.…”
mentioning
confidence: 95%
“…Urinary excretion of water-soluble vitamins such as thiamin, riboflavin and niacin has been used for setting Dietary Reference Intakes (DRIs) in USA and Japan (Food and Nutrition Board, Institute of Medicie, 1998; The Ministry of Health, Labour, and Welfare, 2009). Although pharmacological dose of watersoluble vitamin intake such as vitamin B 2 (Zempleni et al, 1996), nicotinamide (Shibata & Matsuo, 1990) and biotin (Zempleni & Mock, 1999) dramatically increase urinary vitamin levels, a few study had studied about the relationship between several oral dose correspond to dietary intake and urinary excretion of vitamin C (Levine et al, 1996(Levine et al, , 2001). Thus, little attention had been paid to assess the quantitative relationships between intakes and urinary excretion of water-soluble vitamins.…”
Section: Introductionmentioning
confidence: 99%